THE FORMATION OF EXPERIENCE PERFORMING ACTIVITY OF TEACHERS OF MUSIC ART - Labintseva, Larysa P.; Liashenko, Olga D. (Educological discourse, 2015)
The article considers the peculiarities of the formation of experience performing activity of future teachers of musical art; lit methods and techniques of pedagogical influence on students (independent analytical work; intensive development of musical thinking; assessment of concert performances); purpose disclosed, especially the organization performing activities; presents creative tasks that contribute to the formation of experience performing students. The prospect of further research seems theoretical and experimental study of the formation technology of experience, performing activities of future teachers of musical art on the basis of competence approach.